Charisma, Medieval and Modern - Peter Iver Kaufman (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2014)
What is striking about this collection is that all the writers testify to one fact-the extraordinary fruitfulness of Max Weber's idea of charisma. Proof of the capaciousness of the Weberian idea of charisma is its diffusion outside the academic community, although "charisma" as popularized by the media owes little to Weber. These articles reveal, however, that Weberian charisma is indeed relevant to an astonishing range of phenomena. The expansion of charismaތs territory stretches beyond what Max Weber could have imagined.